2017
DOI: 10.1107/s2053230x17011384
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the DNA sequence d(CGTGAATTCACG)2with DAPI

Abstract: The structure of 4',6-diamidine-2-phenylindole (DAPI) bound to the synthetic B-DNA oligonucleotide d(CGTGAATTCACG) has been solved in space group P222 by single-crystal X-ray diffraction at a resolution of 2.2 Å. The structure is nearly isomorphous to that of the previously reported crystal structure of the oligonucleotide d(CGTGAATTCACG) alone. The adjustments in crystal packing between the native DNA molecule and the DNA-DAPI complex are described. DAPI lies in the narrow minor groove near the centre of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…DAPI preferentially binds in the minor groove of double-stranded DNA (dsDNA) with a high AT content. This DNA binding mode has been evidenced by crystallography, NMR data, spectroscopy, and molecular modeling, showing a stable minor-groove binding on (AT) sites of dsDNA. As previously reported by different groups, this interaction mechanism produces drastic changes in the (chir)­optical properties of DAPI. ,, Besides the enhancement of fluorescence of DAPI upon binding, another important consequence is the appearance of an induced circular dichroism (ICD), i.e., the achiral DAPI acquires a circular dichroism signal when bound to the chiral DNA. This ICD signal is observed at the level of a single DAPI bound in the minor groove at a central AATT sequence of short (dodecamer) dsDNA, and it varies with the length and the sequence of the (AT) tract on longer dsDNA .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…DAPI preferentially binds in the minor groove of double-stranded DNA (dsDNA) with a high AT content. This DNA binding mode has been evidenced by crystallography, NMR data, spectroscopy, and molecular modeling, showing a stable minor-groove binding on (AT) sites of dsDNA. As previously reported by different groups, this interaction mechanism produces drastic changes in the (chir)­optical properties of DAPI. ,, Besides the enhancement of fluorescence of DAPI upon binding, another important consequence is the appearance of an induced circular dichroism (ICD), i.e., the achiral DAPI acquires a circular dichroism signal when bound to the chiral DNA. This ICD signal is observed at the level of a single DAPI bound in the minor groove at a central AATT sequence of short (dodecamer) dsDNA, and it varies with the length and the sequence of the (AT) tract on longer dsDNA .…”
Section: Introductionmentioning
confidence: 62%
“…To that aim, we investigate in depth the binding of DAPI to a double-stranded DNA with a model (AT) sequence, through a joint theoretical and experimental approach. This sequence has been selected since it is well-established that DAPI binds to the minor groove on (AT) sequences, whereas an intercalation binding mode could occur on (GC) sequences, which is still controversial. , Besides, a previous study on the interaction between DAPI and single-strand oligonucleotides showed that DAPI interact with sequence containing (AAT) as trinucleotide repeating unit, by favoring the folding of the single strand into a hairpin structure with minor groove binding . In our spectroscopy experiments, we exploited a sequence of 23 base pairs (bp), for which multiple DAPIs can bind in the DNA minor groove.…”
Section: Introductionmentioning
confidence: 99%
“…At a bound MGB:bp ratio of 1:5, PB84 might be quantitatively covered in the context of DNase I degradation because each diamidine 5 directly binds 3−4 bps, and MGBs can inhibit endonuclease activity for an additional 3 bps from their binding site in 3′ direction on the DNA duplex. 67,91 To evaluate whether the decreased protection provided by benzimidazole 3 could be explained by the decreased coverage of PB84, we conducted additional binding experiments. While the affinities of these MGBs for AT tracts are comparable (apparent K D = 1−10 nM), we hypothesized that they might display differential binding to secondary, GCcontaining binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Pt1 and Pt2 could form hydrogen bonds with DNA bases through the NH 3 ligands, while the triphenylamine ligands bind to DNA mainly through hydrophobic and electrostatic interactions (Figure 2B). Interestingly, the conformations of Pt1 and Pt2 matched the major groove and minor groove of DNA, respectively [22] …”
Section: Resultsmentioning
confidence: 99%